Designing a Framework and Strategies to Enhance Individual Innovative Work Behavior : A Case of a Non-Profit in Phnom Penh, Cambodia - Seng, Sonika; Fernando, Maria Socorro C.L. (ABAC ODI JOURNAL Vision. Action. Outcome, 2021)
Innovation has become such a big part of our everyday life that everywhere we go, whatever we do, we tend to seek something new, whether these are new ideas, new experiences, new products, new places, or new technologies. For organizations in highly competitive environments, innovation ensures sustainability and competitive advantage. However, innovativeness comes from the organization's people, so innovative work behavior has rapidly become a significant factor for organizations to explore and establish. This research assesses the needs of five factors that enhance individual innovative work behavior in Pact Cambodia: job resourcefulness, work empowerment, employee motivation, leader-member exchange (LMX), and work engagement. A mixed research methodology was used, and the respondents included the population in the non-profit organization. All 25 employees responded to the survey questionnaire for quantitative research, whereas eight key employees were selected to participate in a focus group discussion. The quantitative data were analyzed using Cronbach's Alpha testing, descriptive analysis, and Priority needs index modified (PNImod). The qualitative data were analyzed using the inter-coding method. The results from PNIMod show that work empowerment, employee motivation, leader-member exchange, and innovative work behavior are the four factors that must be prioritized. The interview questionnaire used appreciative inquiry (AI) questions to further explore work engagement and innovative work behavior. Based on the overall results, the current situation of innovative work behavior is favorable, but PNIModified suggested that some factors should be prioritized to enhance individual innovative work behavior. Therefore, a framework and strategies are presented based on all data results.